2013
DOI: 10.3109/1547691x.2013.763872
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of neutralizing monoclonal antibodies directed against tetanus toxin fragment C

Abstract: Clostridium tetani causes a life-threatening infectious disease by production of tetanus neurotoxin (TeNT), a 150 kDa molecule composed of light (LC) and heavy chain (HC) polypeptides. The TeNT HC contains an N-terminal domain critical for LC translocation and a Cterminal toxin receptor-binding domain known as fragment C. Despite extensive investigations on epitope specificity of anti-TeNT antibodies, the immunodominant neutralizing epitopes of the toxin are poorly defined. This study describes the generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In the present study, we report characterization of seven new and four previously described anti-TeNT specific mAbs 12 all of which react with the tetanus toxin and toxoid. Further characterization of the mAbs with subfragments of the light and heavy chain of TeNT revealed that seven mAbs (1F3E3, 1F2C2, 1F1E12, 1F2C8, 2C9B6, 3B3D9, and 1E4D5) bind to fragment C, while the other four mAbs recognized either LC alone (1F3B3 and 1F3C3), both LC and fragment C (1F4E11), or none of them (5E6B10).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, we report characterization of seven new and four previously described anti-TeNT specific mAbs 12 all of which react with the tetanus toxin and toxoid. Further characterization of the mAbs with subfragments of the light and heavy chain of TeNT revealed that seven mAbs (1F3E3, 1F2C2, 1F1E12, 1F2C8, 2C9B6, 3B3D9, and 1E4D5) bind to fragment C, while the other four mAbs recognized either LC alone (1F3B3 and 1F3C3), both LC and fragment C (1F4E11), or none of them (5E6B10).…”
Section: Discussionmentioning
confidence: 99%
“…12 Briefly, 2000, 1000, 500, 250, 125, and 60 ng/ ml tetanus toxoid was coated on wells of a micotiter ELISA and serial concentrations of mAbs (from 30 to 2000 ng/ml) in blocking buffer were added into each coated well and incubated at 37 °C for 1.5 h. After washing step, all wells were incubated with HRP-conjugated sheep anti-mouse Ig for 1.5 h at 37 °C. Washing was repeated and ODs were measured following addition of TMB substrate solution.…”
Section: Affinity Constant Determinationmentioning
confidence: 99%
See 3 more Smart Citations